Nanoscale bacteriophage biosensors beyond phage display - Lee JW (Dove Medical Press, 2013)
Jong-Wook Lee,1 Jangwon Song,1,2 Mintai P Hwang,1 Kwan Hyi Lee1,2 1Center for Biomaterials, Biomedical Research Institute, Korea Institute of Science and Technology, Seoul, Korea; 2Department of Biomedical Engineering, University of Science and Technology, Seoul, Korea Abstract: Bacteriophages are traditionally used for the development of phage display technology. Recently, their nanosized dimensions and ease with which genetic modifications can be made to their structure and function have put them in the spotlight towards their use in a variety of biosensors. In particular, the expression of any protein or peptide on the extraluminal surface of bacteriophages is possible by genetically engineering the genome. In addition, the relatively short replication time of bacteriophages offers researchers the ability to generate mass quantities of any given bacteriophage-based biosensor. Coupled with the emergence of various biomarkers in the clinic as a means to determine pathophysiological states, the development of current and novel technologies for their detection and quantification is imperative. In this review, we categorize bacteriophages by their morphology into M13-based filamentous bacteriophages and T4- or T7-based icosahedral bacteriophages, and examine how such advantages are utilized across a variety of biosensors. In essence, we take a comprehensive approach towards recent trends in bacteriophage-based biosensor applications and discuss their outlook with regards to the field of biotechnology. Keywords: biosensing, M13 bacteriophage, T4 bacteriophage, bacterial detection, Escherichia coli, SPR sensor